Description Of The Development Of Children Age 4-5 Years In TK Pelangi - Wahyudi; Amirullah; Haerani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2020)
There are several factors that can affect children's development that is not fulfilled, namely, poverty, malnutrition, high levels of family and environmental stress that cause children to be exposed to violence, abuse, and lack of attention and learning opportunities. Children who do not have enough learning time or even do not have the same opportunity to learn can affect their motor development, for example, the brain damage that does not support children to develop motor skills. Lack of research that discusses the developmental picture in children aged 4-5 years, so researchers are interested in doing this research. The purpose of this study was to determine the development of children aged 4-5 years in Pelangi Kindergarten, Anrang Village, Bonto Masunggu Hamlet, Bulukumba Regency in 2020. The method used in this research is descriptive design, which aims to get a picture of the development of children aged 4-5 years in Kindergarten Pelangi, Anrang Village, Kec. Rilau Ale. The population in this study was 31 respondents and the sample size was 31 child respondents in Kindergarten Pelangi, Anrang Village, Kec. Rilau ale. The results obtained are that the researcher found the results of 31 respondents with the highest motor development results in accordance with the number of 21 respondents (67.7%), while with the lowest development there were deviations with respondent 3 (9.7%). The conclusion and suggestion are that there is a description of the development of children in Kindergarten Pelangi, Anrang Village, Kec. Rilau Ale